VINASSE TREATMENT IN BRAZIL FROM 1970S TO 1990S: A LOCK-IN CASE STUDY INTO THE ETHANOL AGROINDUSTRY - Corazza, Rosana Icassatti; Salles-Filho, Sergio (Análise Econômica, 2014)
Adding market value to a former by-product or waste must be an outcome of what is being called an eco-innovation. Vinasse is an important by-product of sugarcane processing in the manufacture of ethanol inBrazil. Until the 1970s, the main destinations of vinasse were surface waters and sacrifice areas. The fabulous augmentation in production of the effluent after the Pro-Alcool and the legal prohibition of vinasse discharges into rivers and other surface waters induced the exploration of new technological possibilities to its destination. During the two subsequent decades, several technological possibilities were under development. In the middle 80s, fertigation was held as the most diffused alternative and the problem was considered solved. This paper exposes the manifold aspects of the problem and the results of an enquiry into the technological trajectory building process that was guided by public and private decision-making focused on the solution of the problem.